Исследование направленности акустического излучения малого беспилотного летательного аппарата - Дмитренко, А. И. (My University, 2018)
In this work, a method is described and the results of studies of the characteristics of the directivity of the acoustic radiation of a small unmanned aerial vehicles on different spectral components for efficient processing of acoustic signals are presented.
Keywords: БПЛА; акустическое излучение